Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences; Vol 4 No 2 (2018): KIU Journal of Social Sciences, Vol. 4 No. 2, June 2018, 2018)
This issue of KIU Journal of Social Sciences focuses on Social Psychology, Educational Psychology, Educational Technology Development Administration, and Judicial Administration. Social psychology is a branch of psychology concerned with how social influences affect how people think, feel, and act. The way we perceive ourselves in relation to the rest of the world plays an important role in our choices, behaviors, and beliefs. Conversely, the opinions of others also impact our behavior and the way we view ourselves. Understanding social psychology can be useful for many reasons. First, we can better understand how groups impact our choices and actions. Additionally, it also allows us to gain a greater appreciation for how our social perceptions affect our interactions with other people. That is why the first part of the Journal addresses issues in Social Psychology such as time management, organizational transparency, gender and career choice and so on. One of the papers argues that it is only by productivity that the real national wealth of a country can increase. The paper therefore, recommended that it is necessary that organization should set out their productivity goal before they even embark on production and the goals must be realistic, specific, comprehensive and meaningful. Section two explores the social and cultural factors that affect the academic performance of students in various institutions of learning in the society. One of the papers found positive and significant relationship between entrepreneurial revolution and entrepreneurial intention; and positive and significant relationship between skills acquisition and entrepreneurial intention. The study concluded that undergraduate students need entrepreneurship skills for them to be able to engage in entrepreneurial activities. The study recommended the need to build an efficient entrepreneurial culture that is essential in the motivation of young graduates to have entrepreneurial intentions. In todayâ€™s world, unpredictability is the only thing which does not change. Things which were true yesterday are not true today and tomorrow is a whole different story. The only way of equipping future generations is to help them tap into their creative wisdom. Here lies the importance of Educational Technology in teaching and learning. Therefeore, section three examines the impact of advancement in technologies on teaching and learning. One of the studies here reveals an average level extent of use of e-learning technologies by the undergraduates; Age was found to be an indicator for e-learning technologies usability; and that there was no significant difference in usability of e-learning technologies for learning based on gender (X-squared (200) = 0.102, p (0.0950) > 0.05). It is recommended therefore, that, the authorities should encourage the undergraduates to utilize e-learning technologies more, in order to accelerate and possess quality improvements on their academic performance, ICT skills and interactivities with peers and lecturers alike. In the Section on Development Administration, it is recommended that organization should set out their productivity goal before they even embark on production and the goals must be realistic, specific, comprehensive and meaningful. This is drawn from the conclusion that productivity is the lifeblood of our economy and key to high standard of living. Productivity growth is important for the wellbeing of future generation.   It is only by productivity that the real national wealth of a country can increase. It has been observed that the administration of justice, in all countries and at all times is a subject broad and difficult, both in its operation and its influence. It is perhaps more indicative, a truer test, of the real temper and spirit, both of the government and the people of the state or country, than any other thing. This is why the papers in the last part of this edition focus on Judicial Administration. On the whole, this issue of KIU Journal of Social Sciences contains papers that have information on all aspects of human endeavour. Collaborative and cooperative approaches are offered as best approaches for dealing with matters that lead to the instability of communities, societies, economies, and the environment. The theoretical analyses provide opportunities to operationalize the theories discussed in the articles. The authorsâ€™ teachings and areas of research must have certainly influenced their perspectives on the diagnoses of the matters they have addressed in their articles.